THE RELATIONSHIP OF NUTRITIONAL STATUS TO URIC ACID LEVEL IN COMMUNITY OF PONDOK PESANTREN AL-HIDAYAH, NGAWI - Lestari, Marselli Widya; Bintarti, Tri Wahyuni (Jurnal Ilmu Kesehatan dan Kesehatan, 2019)
Gout or Gouty Arthritis is a degenerative disease. Gouty arthritis is a clinical syndrome that is caused by deposition of purine crystals in the tissues, due to levels of uric acid (hyperuricemia) in the extracellular fluid that passes through saturation. The etiology of gout arthritis included age, sex, history of medication, obesity, consumption of purine and alcohol. Aging is an important risk factor for men and women. This study uses an analytical-descriptive approach with cross-sectional design. This study was conducted to obtain a relationship between nutritional status and uric acid levels in the community in the area of Al-Hidayah Islamic Boarding School, Ngawi. This research was conducted in Majasem Village, Kendal District, Ngawi Regency, starting from 7 June - 31 August 2018. The results showed that there was a relationship between nutritional status and uric acid levels in the community in the area of Al-Hidayah Islamic Boarding School, Ngawi (p=0,008). Suggestions for further research are bivariate analysis based on gender, knowledge and attitude to response to diet so that other factors that influence can be seen clearly.